1995
DOI: 10.1016/0014-5793(95)00108-l
|View full text |Cite
|
Sign up to set email alerts
|

The sequence of a cytoplasmic intermediate filament (IF) protein from theannelid Lumbricus terrestris emphasizes a distinctive feature of protostomic IF proteins

Abstract: Materials and methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…There are many types of IF protein in vertebrates, most of which can be grouped into five classes: (1) type I (acidic) keratins; (2) type II (basic) keratins; (3) vimentin and desmin; (4) α-internexin and neurofilament proteins; and (5) lamins (Fuchs and Weber, 1994). Lamins are also present in protosomes, suggesting that all IF protein families are derived from a single lamin-like sequence in the common metazoan ancestor (Weber et al, 1989; Dodemont et al, 1994; Bovenschulte et al, 1995). Significantly, however, eukaryotic IF proteins have only been found unambiguously in animals and their relatives (Erber et al, 1998), suggesting that they are an innovation specific to this lineage and not present in the last eukaryotic common ancestor (LECA; see Fig.…”
Section: Filaments Iii: Intermediate Filamentsmentioning
confidence: 99%
“…There are many types of IF protein in vertebrates, most of which can be grouped into five classes: (1) type I (acidic) keratins; (2) type II (basic) keratins; (3) vimentin and desmin; (4) α-internexin and neurofilament proteins; and (5) lamins (Fuchs and Weber, 1994). Lamins are also present in protosomes, suggesting that all IF protein families are derived from a single lamin-like sequence in the common metazoan ancestor (Weber et al, 1989; Dodemont et al, 1994; Bovenschulte et al, 1995). Significantly, however, eukaryotic IF proteins have only been found unambiguously in animals and their relatives (Erber et al, 1998), suggesting that they are an innovation specific to this lineage and not present in the last eukaryotic common ancestor (LECA; see Fig.…”
Section: Filaments Iii: Intermediate Filamentsmentioning
confidence: 99%
“…In contrast to vertebrates, protostomic phyla display cytoplasmic IF proteins which have an extra 42 residues in their coil 1b domain and in most cases harbor a lamin homology segment of 120 residues in their tail domain. This was originally documented for molluscs, nematodes and annelids (Weber et al, 1988(Weber et al, , 1989Dodemont et al, 1990Dodemont et al, , 1994Szaro et al, 1991;Way et al, 1992;Tomarev et al, 1993 Bovenschulte et al, 1995;Johansen and Johansen, 1995) and more recently the long coil 1b version has also been found in eight further protostomic phyla (D.R., K.W., A. Erber and M. Bovenschulte, unpublished results). Parallel work showed that the short coil 1b version present in all vertebrate IF proteins also holds for the eight cytoplasmic IF proteins established for the cephalochordate Branchiostoma (Riemer et al, 1992(Riemer et al, , 1998.…”
Section: Introductionmentioning
confidence: 57%